Brief stress impairs recognition memory through amygdalar activation in animals with medial prefrontal cortex lesions. (14th September 2020) - Park, Jung-Cheol; Jeon, Yong-Jae; Kim, Jeansok J.; Cho, Jeiwon; Choi, Dong-Hee; Han, Jung-Soo
Highlights: A brief stress (20-min uncontrollable) does not impair recognition memory. A prolonged stress (60-min uncontrollable) impairs recognition memory. A brief stress induces higher c-Fos levels in the amygdala of the mPFC-lesioned animals. A brief stress impairs recognition memory in the mPFC-lesioned animals. No effects of mPFC lesions on pre-stress and post-stress CORT levels. Abstract: The medial prefrontal cortex (mPFC) is thought to exert inhibitory control over stress-induced activation of the amygdala and neurocognitive effects. As evidence to support this, we examined how exposure to either a brief or prolonged stress affected on amygdalar c-Fos levels and recognition memory of animals with mPFC chemical lesions. mPFC-lesioned and sham-operated animals were subjected to either a brief 20-min restraint+20 tailshocks or a prolonged 60-min restraint+60 tailshocks. Post-stress performances in the object recognition memory and c-Fos immunoreactivity in the amygdala were then assessed. In sham-operated animals, the object recognition memory was reliably impaired following the prolonged, but not following the brief stress exposure. On the other hand, in mPFC-lesioned animals, the brief stress significantly impaired recognition memory and enhanced c-Fos expression in the amygdala. Present findings of loss of mPFC activity exacerbating stress effects provide causal evidence that the mPFC exerts inhibitory control on stress.